The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.jpcc.7b01519
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Optical Bistability and Tristability in Nonlinear Graphene-Wrapped Nanospheres

Abstract: Based on full-wave scattering theory with self-consistent mean field approximation, we study the optical multi-stability of graphene-wrapped dielectric nanoparticles. We demonstrate that the optical bistability (OB) of the graphene-wrapped nanoparticle exist in both near-field and far-field spectra, and show the optical multi-stability arising from the contributions of higher-order terms of the incident external field. Moreover, both the optical stable region and the switching threshold values can be tuned by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…This can be confirmed in the transmission plot in Figure 2e, in which at the critical point c 1 the lower branch shows 0 transmission, and a slight increase in power causes an abrupt jump to unitary transmission. This behavior has potential in optical applications like optical limiters, nanoswitches [22,43] and nonreciprocal devices [23]. Similar to Figure 2c, we plot in Figure 2f the transmission as the input power increases for different frequencies.…”
Section: Principle Of Operation Of Nonlinearity-based Nonreciprocal Devices Based On Coupled Fano Metasurfacessupporting
confidence: 56%
“…This can be confirmed in the transmission plot in Figure 2e, in which at the critical point c 1 the lower branch shows 0 transmission, and a slight increase in power causes an abrupt jump to unitary transmission. This behavior has potential in optical applications like optical limiters, nanoswitches [22,43] and nonreciprocal devices [23]. Similar to Figure 2c, we plot in Figure 2f the transmission as the input power increases for different frequencies.…”
Section: Principle Of Operation Of Nonlinearity-based Nonreciprocal Devices Based On Coupled Fano Metasurfacessupporting
confidence: 56%
“…Without loss of generality we provide quantitative estimations of parameters for the following configuration: a pair of identical spherical graphene-wrapped nanoparticles made of BaF2. We have chosen such configuration since graphene is a promising highly nonlinear plasmonic material [27][28][29] and BaF2 is transparent and almost dispersion-free in the middle infrared domain where graphene demonstrates plasmonic resonances (see Supplementary Materials for details). In experiment, graphene-wrapped nanospheres can be obtained by using layer-by-layer self-assembly or precursor-assisted chemical vapor deposition [30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we will treat it as a conducting film with surface conductivity r with a realistic approximation [40,41]. Hence, the source-free boundary conditions could be applied for the monolayer graphene-coated core-shell [37,38]. The coefficients A, B, and C are determined by applying the boundary conditions at the inner and outer boundary after some algebraic calculations…”
Section: Theoretical Model and Methodsmentioning
confidence: 99%
“…Recently, it is shown that in addition to strengthening the local plasmonic fields, graphene also can generate large nonlinear effects [32][33][34][35][36]. OB in graphene-based composite consisting of graphene-wrapped dielectric spherical nanoparticles has been studied theoretically [37,38]. In optoelectronics aspects, there also has been a great deal of interest in studying the optical properties of graphene due to its abundant potential applications within a wide spectral range from terahertz to visible frequencies [37].…”
Section: Introductionmentioning
confidence: 99%